(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
Based on concepts from Nogueira and Cruz, Bezelga & Menezes, the article examines the practices of the theatre group that occupied an antique former Silk Factory in Barbacena, providing sustainability to the heritage. Once manufacturing activities were closed, government agencies occupied the buildings. However, in the 1990s, the mansions remained unoccupied until appropriation by the Ponto de Partida Theatre Group in 1998. To restore the deactivated industrial heritage, the Group involved the community of Barbacena in donations and competitions, and in 2004, it occupied Pavilion 1. After Pavilion 2´s restoration, the Bituca University of Popular Music was inaugurated, a tribute to Milton Nascimento, and, finally, the group installed the community library in Pavilion 3.